Competencies Framework For The Property Manager Of Shopping Malls - Marliah, Ab Wahab; Mariah, Awang; Aminah, Mohsin; Wilson Rangga, Anthony Jiram; Siti Radiaton, Adawiyah; Mohd Shahril, Abdul Rahman (International Journal of Scientific & Technology Research, 2020)
The property management profession in Malaysia is registered under the Akta Penilai, Pentaksir, Ejen Harta Tanah dan Pengurus Harta 1981 (Akta 242)/ Valuers, Appraisers, Real Estate Agents and Property Managers Act 1981 (Act 242). A property manager is required to carry out management and control of any land, building and any interest in the land or building, excluding business management based on the property on behalf of the owner for a fee. In Malaysia, property managers have previously been free to manage their property under their custody, most of whom manage the assets on the basis of their own guidelines and standards. Therefore, in order to address these issues, this study was conducted in order to develop a competencies framework for property managers in the shopping mall. Proposed framework that based on knowledge, skills, abilities and other characteristics (KSAOs), could assist the organization in determining the competencies of property managers in their shopping centers for day-to-day tasks as well as for the purpose of hiring. Future research on the relationship between knowledge, skills, abilities and other characteristics of job performance is recommended.